(untitled) (Revista Contexto & Saúde, 2025)
Objective: to analyze the knowledge of Primary Health Care (PHC) nurses about the relationship between environment, health, and COVID-19. Methods: This is a cross-sectional analytical study conducted with PHC nurses in Brazil. Data were collected from September 14, 2021, to April 15, 2022, through a self-administered questionnaire and analyzed using prevalence ratios and a Poisson regression model. Results: 253 nurses participated in the study. It was found that most nurses are aware of the relationship between environmental health and human health. In addition, nurses with more than 20 years of experience had, on average, a 19% higher prevalence of perceiving the difficulties that the assisted population faced in understanding measures to prevent COVID-19 infection (p < 0.01). Conclusion: Most nurses are aware of the relationship between environmental issues and COVID-19. However, despite the relevance of environmental impacts on health, there is still a lack of coordination with practical nursing activities.